Legal Culture for Exercising Constitutional Rights - Danielyan , G. (Bulletin of Yerevan University C: Jurisprudence, 2017)
Components of legal culture for exercising and defending rights, problems existing in this field and possible ways for their solution are discussed in the article presented. The following position is endorsed by the author: in the process of exercising rights it is necessary to reduce significantly burdening of physical person or legal entity with various liabilities. In some cases it is also necessary to eliminate their liability to act as an initiator for exercising their rights, for example when dealing with the their liability to submit application. At the same time, those criteria that may predict the distinct scope of cases when the persons should act on their own initiative for exercising rights are systematically presented in the article. According to the approaches reflected in the article in case of absence of relevant mechanisms and procedures for exercising rights not only exercise and protection of rights but also efficiency of administration become vulnerable as far as it results in great inappropriate financial expenses and bureaucratic foot-dragging.
Keywords: exercise of constitutional law, protection of right, legal culture, mechanism for exercising rights, administrative way of defending rights, protection of rights judicially, administrative proceedings, administration